Evaluation of Drug Accuracy and Cardiac Drug Dose Accuracy in Heart Failure Patients Hospitalized in Samarinda: Evaluasi Ketepatan Obat Dan Dosis Obat Jantung Pada Pasien Gagal Jantung Di Instalasi Rawat Inap Rumah Sakit Samarinda - Hanifa, Deasy Nur Chairin; Riansyah, Novita Angelia (Universitas Tadulako, 2024)
Background: Heart failure is a condition where the heart is unable to pump blood to the tissues to meet the body's metabolic needs. Heart failure has a variety of therapies and drug options available, so careful consideration is needed in selecting drugs for heart failure patients. Evaluation is carried out to identify problems with the accuracy of drug use and dosage accuracy. The many types of drugs available present its their problems in the use of drugs, especially in the selection and use of drugs that are effective, correct, and safe. Inappropriate and rational use of drugs can increase morbidity and mortality. Objectives: To determine the accuracy of drugs and heart drug dosages in patients with heart failure at the inpatient installation of Samarinda Medika Citra Hospital. Material and Methods: This research is a descriptive observational study with retrospective data collection in 2022. The sample consisted of all adult heart failure inpatients who met the inclusion criteria of 60 patients. Results: The results of the study showed that out of 60 patients, the accuracy of therapy included 93% of the correct drug and 88% of the correct dose. The heart failure drugs used were furosemide (39%), spironolactone (19%), digoxin (18%), candesartan (15%), captopril (4%), bisoprolol (3%), and lisinopril (2%). Conclusions: From the research results, it was found that 93% of the drug accuracy and 88% of the drug dose accuracy in heart failure patients.